2004
DOI: 10.1542/peds.2004-0962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nurse Home-Visiting on Maternal Life Course and Child Development: Age 6 Follow-Up Results of a Randomized Trial

Abstract: This program of prenatal and infancy home-visiting by nurses continued to improve the lives of women and children at child age 6 years, 4 years after the program ended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
335
1
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 436 publications
(355 citation statements)
references
References 34 publications
11
335
1
8
Order By: Relevance
“…Social support is a concept that is perhaps less familiar to physicians. However, randomized trials of the provision of social support to new parents have shown lasting positive impacts for children, at least when done by nurses [49][50][51]. At this point, it seems reasonable to recommend an opportunistic approach of awareness, screening as much as possible, and intervening where leverage is available, based on physician, patient, and local resources.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is a concept that is perhaps less familiar to physicians. However, randomized trials of the provision of social support to new parents have shown lasting positive impacts for children, at least when done by nurses [49][50][51]. At this point, it seems reasonable to recommend an opportunistic approach of awareness, screening as much as possible, and intervening where leverage is available, based on physician, patient, and local resources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Nurse-Family Partnership 46 provided services to low-income, first-time mothers to improve their health and behaviours while pregnant and strengthen parenting skills when children were infants. All other interventions targeted both parents and children to simultaneously enhance protection and reduce family and individual risks.…”
Section: The Science Of Preventionmentioning
confidence: 99%
“…53 Second, women we identified as high risk because of pregnancy complications may be eligible for postpartum home visits aimed at improving newborn care and outcomes, but which could aid their successful transition into outpatient care and prevent ER use. In fact, studies in socially or medically complicated women have demonstrated that a benefit of postpartum home visits is a reduction in maternal acute care visits, postpartum hospital stays, costs, 54 repeat pregnancies, [55][56] and months on Medicaid. 57 The Affordable Care Act's Maternal, Infant, and Early Childhood Home Visiting Program was recently expanded, presenting an opportunity to link maternal and child care to improve outcomes for both.…”
Section: Commentsmentioning
confidence: 99%